PARENTS’ MOTIVATIONAL FACTORS FOR SENDING THEIR CHILDREN TO PRIVATE ISLAMIC SCHOOL - Firdianty Afifah Az Zahro; M. Darojat Ariyanto; Mohammad Zakki Azani (Universitas Muhammadiyah Surakarta, 2019)
Children mostly receive their first education from their parents. In Islamic intellectual tradition, the most important part to be instilled first in man’s life is the teaching of religious beliefs, of morality (adab). When the children have to pursue further studies, their parents are playing important roles in the process of choosing educational institution for their children. In this paper discusses specifically on parents’ reasons for sending their children to Muhammadiyah Junior High School 4 of Surakarta Academic Year 2019/2020. This is a field study and using a descriptive quantitative approach by distributing closed questionnaires via Google form. The result shows that the parents really hope that their children are good in understanding general knowledge within Islamic educational framework. If the parents’ wishes can be successfully instilled into their children in the educational process and hope it can be successfully achieved, it means the vision and mission of the school are fulfilled accordingly.